Blood Biomarkers for the Diagnosis of Neurodegenerative Dementia - A Systematic Review - Ana Filipa Santos Oliveira (2022)
Neurodegenerative dementia diagnosis is often challenging due to similar clinical presentations and neuropathological overlap. Disease specific biomarkers could enhance diagnostic accuracy. To date, only Alzheimer's Disease (AD) has core cerebrospinal fluid (CSF) validated biomarkers (Aβ42, T-tau and P-tau). However, CSF analysis procedures and positron emission tomography imaging modalities are either invasive or high-priced, and routinely unavailable. Thus, diagnosis usually relies only on clinical criteria. Easily accessible disease biomarkers would be of utmost value for accurate differential diagnosis of dementia subtypes. Here, we conducted a systematic literature search to identify blood-based biomarkers that could help differentiating AD from Frontotemporal Lobar Degeneration (FTLD), including Frontotemporal Dementia (FTD), or AD from Dementia with Lewy bodies (DLB). Three databases (PubMed, Scopus, and Web of Science) were searched. Studies assessing blood-based biomarkers levels in AD versus FTLD, or AD versus DLB, and its diagnostic accuracy, were selected. When the same biomarker was assessed in three or more studies, a meta-analysis was performed. QUADAS-2 criteria were used for quality assessment. Twenty studies were included in this analysis. Collectively, 905 AD patients were compared to 1262 FTLD patients, and 209 AD patients were compared to 246 DLB patients. Regarding biomarkers for AD versus FTLD, excellent discriminative accuracy (AUC>0.9) was found for p-tau181, p-tau217, synaptophysin, synaptopodin, GAP43 and calmodulin. The microRNAs miR-107/miR-335-5p and miR-127-3p, neurogranin, synaptotagmin and GFAP also demonstrated good accuracy (AUC=0.8-0.9). For AD versus DLB distinction, only miR-21-5p and miR-451a achieved excellent accuracy (AUC>0.9). This systematic review highlighted state-of-the-art blood-biomarkers that might play an important role in the diagnosis of neurodegenerative dementia. Although encouraging results were found for several biomarkers, alone or in combination, further research is warranted. Prospective longitudinal designs and consensual protocols, comprising larger cohorts and homogeneous testing modalities across centres are essential to validate the clinical value of these blood-derived biomarkers.